Yield and quality of milk and udder health in Martina Franca ass: effects of daily interval and time of machine milking - Giovanni Martemucci; Michele Pizzillo; Salvatore Claps; Rosanna De Petro De Petro; Angela Gabriella D’Alessandro (Italian Journal of Animal Science, 2010)
Twenty asses of Martina Franca breed, machine milked twice a day, were used to assess the influence of milking interval (3-h, 5-h, and 8-h; N=5) and time (700, 1200 and 1900) on milk yield and udder health. Individual milk samples were taken to determine fat, protein and lactose con- tent. Sensory analysis profile was also assessed. Milk’s total bacterial count (TBC), somatic cell con- tent (SCC) and udder’s skin temperature were considered to assess udder health. Milk yield increases by 28.4% (P<0.01) with a milking interval from 3-h to 8-h and is higher (P<0.01) at morning milking. The maximum milk yield per milking corresponds to 700 milking (1416.9 mL) thus indicating a circa- dian rhythm in milk secretion processes. Milking intervals of 5 and 8 hours cause a decrease (P<0.01) in milk fat and lactose content. The 8-h interval leads to an increase (P<0.01) in SCC but without any significance for the health udder. No alterations about CBT, clinical evaluation and temperature of ud- der were observed. Milk organoleptic characteristics were better in the 3-h interval milking.